Creating a system of economic incentives for the implementation of innovative products and solutions - DOLHOPOLOV, Volodymyr (Ways to Improve Construction Efficiency, 2025)
The formation of an effective system of economic incentives for the implementation of innovative products and solutions is a fundamental condition for developing an innovation-driven economy and enhancing the competitiveness of enterprises. Its essence lies in creating a balanced structure of direct and indirect mechanisms of influence that provide not only financial support for innovations but also a favorable institutional environment for their realization. Such incentives act as moderators of economic behavior, directing economic agents toward adopting innovative decisions even under conditions of high uncertainty. The system of economic incentives is based on the combination of financial, tax, administrative, informational, and regulatory instruments. Its key characteristic is adaptability – the ability to respond to changing market and technological conditions. Within the innovation stimulation model, a significant role is played by the interrelationship between the size of the incentive, the level of risk, and the innovation activity of enterprises. It has been established that even strong financial incentives lose their effectiveness in environments with high institutional risks or low trust in the regulatory system. The institutional environment serves as the main filter for the perception of incentives. When effective legal guarantees, property rights systems, and mechanisms for monitoring funding compliance are absent, economic incentives fail to translate into real actions. Therefore, the economic efficiency of incentives should not be considered in isolation but rather in correlation with the quality of institutions, the level of transparency, and the governance structure. The development of an incentive system requires a balance between supply-side instruments (tax benefits, subsidies, grants) and demand-side tools (public procurement of innovations, guarantees, export support). It is advisable to combine short-term financial measures with long-term mechanisms for building innovation infrastructure – technology parks, incubators, and venture funds. Such an approach creates an “affordable risk” environment that facilitates the transition from isolated innovative actions to a sustainable innovation culture. The proposed concept of the incentive system covers three levels: the state (strategic and regulatory), corporate (investment and operational), and partnership (cluster and network). Each level involves specific mechanisms – from tax credits and innovation vouchers to programmed financing and repayable grants. Their effectiveness is determined by the system’s ability to synchronize the interests of investors, innovators, and society.